Muscle Expression of SOD1G93A Modulates microRNA and mRNA Transcription Pattern Associated with the Myelination Process in the Spinal Cord of Transgenic Mice - Dobrowolny, Gabriella; Bernardini, Camilla; Martini, Martina; Baranzini, Mirko; Barba, Marta; Musarò, Antonio (Frontiers in Cellular Neuroscience, 2015)
A crucial system severely affected in several neuromuscular diseases is the loss of effective connection between muscle and nerve, leading to a pathological non-communication between the two tissues. One of the best examples of impaired interplay between muscle and nerve is Amyotrophic Lateral Sclerosis, a neurodegenerative disease characterized by degeneration of motor neurons and muscle atrophy. Increasing evidences suggest that damage to motor neurons is enhanced by alterations in the neighboring non-neuronal cells and indicate that altered skeletal muscle might be the source of signals that impinge motor neuron activity and survival. Here we investigated whether muscle selective expression of SOD1G93A mutant gene modulates mRNAs and miRNAs expression at the level of spinal cord of MLC/SOD1G93A mice. Using a Taqman array, the Affymetrix Mouse Gene 2.0 ST approach and the MiRwalk 2.0 database, which provides information on miRNA and their predicted target genes, we revealed that muscle specific expression of SOD1G93A modulates relevant molecules of the genetic and epigenetic circuitry of myelin homeostasis in spinal cord of transgenic mice. Our study provides insights into the pathophysiological interplay between muscle and nerve and supports the hypothesis that muscle is a source of signals that can either positively or negatively affect the nervous system.